Families’ Psychological Fragility during an Emergency - Qona’ah, Arina; Rachmawati, Septi Dewi; Chan, Chong Mei (International Journal of Psychosocial Rehabilitation, 2020)
Critical conditions due to traffic accidents are situational crises for families which result in a disruption in the stability of the equilibrium and cause psychological problems to family members. This study aimed to explore the psychological reaction experienced by the families of traffic accident victims who were treated in the emergency room in a critical condition. A qualitative interpretive phenomenology approach was applied as the research design. Purposive sampling technique was used to recruit participants according to the inclusion criteria. The inclusion criteria were the nuclear family, families of critically traumatized patients and who were able to communicate. There were 10 participants involved in this study. Data collection was conducted via the semi-structured interviews. Data were analyzed by Braun and Clarke Thematic Analysis. Five overarching themes emerged from this study. Firstly, the family feels "denial reaction to an accident" and when the patient is critical, they become "fearful of losing a loved one". This situation makes them "vulnerable to fragility" and in the end "give up hope". The physical condition of the patient and the loss of family members can be the traumatic effect of an accident. Interestingly, we found that a critical situation leads to a closer relationship within family members. The emotional response felt by the family member provides an overview of the family’s feelings in a state of grieving and they need support from other people including health care providers. Appropriate coping mechanisms and family support are important to prevent fragility in the families of critical patients in the emergency room.